Pemanfaatan Sistem Informasi Geografi Untuk Analisis Risiko Longsor di Kecamatan Tirtomoyo, Kabupaten Wonogiri - Surastuti, Yunita; , Dr. Kuswaji Dwi Priyono, M. Si (2016)
Landslide is one of disasters that often occur and relatively evenly spread almost all over Indonesia. Tirtomoyo Sub-District in Wonogiri Regency is an area that has hilly and mountainous morphology, so at risk of landslide. Supported by geographic structure, Tirtomoyo Sub-District located in mountainous area with the majority of houses near the cliffs, so it appears the lanslide prone area. This study has two purpose : (1). Determine the risk level and distribution of lanslide risk areas, (2). Analize the most dominant factor that influencing the landslide. Data used include DEM SRTM, ALOS Imagery, soil type, rock type, rainfall, BPS data, PODES. There are three factors used to determine the landslide risk, such as hazard, vulnerability, and capacity made from several parameters. Analysis process done with Geographic Information System, namely the overlay technique using ArcGis 10.2 between the parameters that have been made. This study produced two results, namely the distribution and level of landslide risk is presented in the form of geospatial information or a map and analysis of the dominant factors affecting the landslide. The risk level divided into three classes, low, medium, and high. High risk has a percentage of 56%, while 7.8% lower. The dominant factor is determined by using the total score is the highest among all of the factors. The dominant factor affecting landslide is kind of reddish brown soil litosol complex, which is located almost evenly throughout the District of Tirtomoyo. Keyword : Landslide, Risk, and Geographic Information System.